2012
DOI: 10.1002/cne.23059
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal organization of the hemiellipsoid body of the land hermit crab, Coenobita clypeatus: Correspondence with the mushroom body ground pattern

Abstract: Malacostracan crustaceans and dicondylic insects possess large second-order olfactory neuropils called, respectively, hemiellipsoid bodies and mushroom bodies. Because these centers look very different in the two groups of arthropods, it has been debated whether these second-order sensory neuropils are homologous or whether they have evolved independently. Here we describe the results of neuroanatomical observations and experiments that resolve the neuronal organization of the hemiellipsoid body in the terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 81 publications
6
100
0
Order By: Relevance
“…Across insects, mushroom bodies and their crustacean homologues are exceptionally immunoreactive to antibodies raised against DC0 [2,56]. This molecular character also corresponds across all arthropod groups and lophotrochozoan phyla including annelids, Platyhelminthes and nemerteans [3].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Across insects, mushroom bodies and their crustacean homologues are exceptionally immunoreactive to antibodies raised against DC0 [2,56]. This molecular character also corresponds across all arthropod groups and lophotrochozoan phyla including annelids, Platyhelminthes and nemerteans [3].…”
Section: Introductionmentioning
confidence: 84%
“…A characteristic of these centres is that afferents and efferents define discrete domains through the lobes, from which centrifugal cells provide reafferent feedback to more distal levels (figure 1a). The same ground pattern exists in crustaceans (figure 1b) in dome-like centres referred to as hemiellipsoid bodies, the organization of which genealogically corresponds to mushroom bodies [1,2]. Mushroom bodies, like those of insects, occur in Lophotrochozoa, as in the annelid's asegmental and supraesophageal brain ('acron') where paired mushroom bodies are supplied by relays from olfactory glomeruli [3].…”
Section: Introductionmentioning
confidence: 89%
“…Mushroom bodies are higher brain centers located in the first brain segment of all arthropods and their common ancestors (Kenyon 1896;Strausfeld et al 2006;Strausfeld 2012;Wolff et al 2012). In insects, they are important in contextual information processing, learning, and memory (fruit flies: de Belle & Heisenberg 1994;Zars et al 2000;Pascual & Preat 2001;Heisenberg 2003;honey bees: Erber et al 1980, Menzel 2001cockroaches: Mizunami et al 1998).…”
Section: Introduction To the Ordermentioning
confidence: 99%
“…Speculations that the mushroom bodies in insects and the hemiellipsoid bodies in crustaceans are homologous structures have gained more support in later years, with evidence of similar correspondences between the morphology, structure and immunoreactivity of the two structures (Strausfeld, 2012, Wolff et al, 2012.…”
Section: Hemiellipsoid Bodiesmentioning
confidence: 99%
“…In crustaceans, the olfactory globular tracts (OGT) terminate in neuropils that arise dorsally from the lateral protocerebrum which are called hemiellipsoid bodies (Sullivan and Beltz, 2001b, Sullivan and Beltz, 2001a, Sullivan and Beltz, 2004. These hemiellipsoid bodies have been suggested to be homologues of the mushroom bodies in insects and morphology, ultrastructure and immunoreactivity advocate the same (Wolff et al, 2012). Recent studies have also revealed that the mushroom bodies are capable of modality switching, processing visual information instead of olfactory information in aquatic species which generally lack antennal lobes (Lin and Strausfeld, 2012).…”
Section: Introductionmentioning
confidence: 99%